Another New Bent-toed Gecko, genus Cyrtodactylus Gray 1837 (Squamata: Gekkonidae), from Borneo - Riyanto, Awal; Fauzi, Muhammad Alif; Sidik, Irvan; Mumpuni; Irham, Mohammad; Kurniawan, Nia; Ota, Hidetoshi; Okamoto, Taku; Hikida, Tsutomu; Grismer, L. Lee (Zootaxa, 2021)
To reveal the diversity of Indonesian bent-toed geckos, we pay attention to Kalimantan (Borneo)—an island which has received less attention than other Indonesian islands such as Sumatra, Java, Sulawesi, the Moluccas, and the Lesser Sunda archipelagos. About 30 years after Hikida (1990) described three new Cyrtodactylus from Borneo, four more species were described, namely C. limajalur and C. muluensis in 2019, and C. hantu and C. miriensis in 2021, all by Davis et al. Through examination of the collection at MZB and three addition specimens collected from Tawau, we found several undescribed species, one of which we describe here. This new species is easily differentiated from all other congeners by the combination of the following characters: maximum SVL of at least 65.8 mm; no tubercles on dorsal surface of upper arm; tubercles present in the ventrolateral body folds; 28–30 paravertebral tubercles; 17–20 longitudinal dorsal tubercle rows; 39–46 ventral scale rows at midbody; 17–19 subdigital lamellae on fourth toe; precloacal pit with 5–7 pores in males arranged in a wide Λ-shape but absent in females; no enlarged transverse median subcaudals; paired dark brown semilunar-shaped markings on the upper nape. Further study is needed to reveal its molecular phylogenetic position and biogeographical history.